Primary amyloidosis and severe intrahepatic cholestatic jaundice. Issue 9 (September 1994) - Peters, R A; Koukoulis, G; Gimson, A; Portmann, B; Westaby, D; Williams, R
Abstract : Liver involvement in systemic amyloidosis is frequent but is rarely of clinical importance. Five patients with severe cholestatic jaundice are described and an additional 20 from published reports are reviewed. The most frequent presenting symptoms were lethargy and abdominal pain, which were present for a median of 11 months before the onset of jaundice. Hepatomegaly, usually marked, was present in 92%, with ascites in 56% of the cases. The serum bilirubin concentration was noticeably high and the serum globulin low. Histology of the liver showed considerable perisinusoidal deposition with a slight predilection for the periportal area. Two patients presented with predominant centrilobular deposition. Congo red staining was not uniformly positive. A variety of treatment regimens was tried but median survival was only three months from the onset of jaundice.